G268 Prenatal and perinatal risk factors for childhood disability in a rural Nepali birth cohort. (27th April 2016) - Haworth, E; Tumbahangphe, KM; Costello, A; Manandhar, D; Adhikari, D; Budhathoki, B; Shrestha, DK; Sagar, K; Heys, M
Abstract : Aim: There has been a renewed focus globally on neonatal mortality as the deadline for the Millennium Development Goals approaches. 1 Little is known about the neurodevelopmental consequences for survivors of complications in pregnancy, labour and the neonatal period in in low income countries outside of small, selective and typically urban facility studies. 2 We ask which antenatal, birth and neonatal factors are associated with disability at age eleven in a large community recruited birth cohort from rural Nepal. Methods: This cohort of 6, 285 live births was recruited during a cluster randomised control trial of participatory women's group on neonatal mortality. 3, 4 At age eleven 4, 219 children were available for detailed follow up assessment including disability screening, with a retention rate in survivors of 72% (Figure 1 ). Disability was assessed by face to face interview using the newly developed UN/UNICEF Module on Child Functioning and Disability. 5 To minimise the risk of posthoc testing first a list of hypothesised risk factors for adverse outcome was drawn up which was then consummated with the available data (Table 1 ). Factors with a univariate significance of <0.1 then underwent multivariable logistic regression modelling with disability as the outcome, adjusting for trial allocation and socioeconomic status. Results: Overall prevalence of disability was 7.4%. Maternal underweight (Odds Ratio (OR) 1.44 (95% confidence interval 1.01–2.08)), maternal cohabitation under 16 years of age (OR 1.50 (1.13–2.00)), increased weight at 1 month (per standard deviation OR 0.82 (0.71–0.95)) and reported diarrhoea and vomiting within the first 4 weeks of life (OR 2.48 (1.58–3.89)) were significantly associated with disability. The majority of hypothesised risk factors, including prematurity, were not significant on multivariable analysis (Table 2 ). Conclusions: The relationship between poverty, maternal malnutrition and poor neurodevelopmental outcome is well recognised 6 and our findings here emphasise the importance of breaking this cycle. The lack of association of most recognised risk factors for adverse outcome in high income settings may be due to high mortality and survival bias. As the neonatal mortality rate falls in countries like Nepal future research will need to revisit the relationship between birth environment and disability.